Analysis of Instagram Social Media Management @livingintelkom in Forming Public Opinion on the Digistar Class Program - Marvella, Sadira Ayu; Abdurrahman, Muhammad Sufyan (Program Studi Ilmu Komunikasi FBIK Unissula, 2024)
Digistar Class is a free and flexible online class program organized by PT Telkom Indonesia (Persero) Tbk through the Living in Telkom community, aiming to improve digital skills (hard skills & soft skills) for students and fresh graduates. This study analyzes Instagram social media management @livingintelkom in shaping public opinion towards the Digistar Class Program. Based on the Circular Model of SOME theory and the public opinion theory of Leonard W. Doob, this study identifies that @livingintelkom accounts successfully increase participation and positive sentiment through the strategy of